Detecção e identificação de Pseudomonas spp. em sementes de trigo - Raab, Marisseia (2014)
There are several pathogens that cause diseases in wheat (Triticum aestivum). Among these are the bacteria, which are widespread in all the wheat producing regions of the world and Brazil, with emphasis on the genera pseudomonas and xanthomonas. In this sense, this work aimed to detect and identify the presence of cultivars of wheat grown in Rio Grande do Sul. Seed samples were obtained from three sites (Ijuí, Passo Fundo and Tupanciretã) and from three harvests (2010, 2011 and 2012) ), Including six cultivars (Mirante, Quartz, BRS 327, BRS 331, BRS Guamirim and Ivfim). For the analysis, nine samples were used. The analytical process used the acrylic boxes, Gerbox type, containing medium of culture 523, where 25 seeds per Gerbox were distributed, making 500 seeds of each sample and each cultivar. Next, the bacteria isolates were purified in 523 culture medium and identified by comparison with the "Type" bacteria. Biochemical, physiological and pathogenicity tests were carried out on wheat plants, as well as the use of the Bactray Kit and the Biolog GEN III Micro-Plate identification system. Three groups of isolates with similar characteristics were formed. Six isolates of bacteria with Pseudomonas genotypes were detected in all the seed samples analyzed. Group 2 isolates had a negative oxidase reaction, but arginine dihydrolase and a hypersensitivity reaction in positive tobacco plants. The isolates of group 3 presented a positive reaction for oxidase, arginine dihydrolase and hypersensitivity reaction in tobacco plants. In 67% of the samples, there were isolates of group 1, identified as P. fuscovaginae, characterized by the positive reaction to oxidase and arginine dihydrolase, a positive reaction to hypersensitivity in tobacco plants and their inability to use 2-ketogluconate and to produce acid From inositol. All isolates were pathogenic to wheat plants.